Address and traffic dynamics in a large enterprise network - Karagiannis, Thomas; Mortier, Richard (IEEE LAN/MAN Workshop, 2008)
Despite the centrally-managed nature of and critical infrastructure provided by enterprise networks, analyses of their characteristics have been limited. In this paper we examine the dynamics of enterprise networks from two distinct perspectives, namely traffic and addressing. Using a large packet trace spanning approximately 3.5 weeks coupled with diverse other data sources, we pose and answer a series of questions pertinent to understanding the aforementioned aspects of today’s enterprise networks. Our analysis results reveal characteristics regarding the geographical spread of traffic observed at a site in the enterprise network, the validity of the client-server model and mobility patterns within the Enterprise. Finally, we discuss the implications of our findings for tasks such as network management and dimensioning.